2018
DOI: 10.20944/preprints201811.0100.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geotechnical Properties of Lateritic Soil Stabilized with Periwinkle Shells Powder

Abstract: This study used eco-friendly materials known as Periwinkle Shell Powder (PSP) in stabilizing the engineering properties of lateritic soil. Preliminary test was performed on the un-stabilized lateritic soil for the purposes of identification and classification (natural moisture content, liquid limits, plastic limits, and plasticity index). The engineering tests were conducted on the lateritic soil stabilized with additions of (2, 4, 6, 8 and 10 %) PSP and OPC respectively. The result showed that cement gave a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Dauda et al (2018) also contributed to the global efforts being made in encouraging environment-friendly processes in construction, by carrying out an investigation into the stabilization of lateritic soil using Periwinkles Shell Powder (PSP). As much as the incorporation of PSP can help improve clean process in construction, it is not widely available across Africa and non-coastal areas.…”
Section: Previous Workmentioning
confidence: 99%
“…Dauda et al (2018) also contributed to the global efforts being made in encouraging environment-friendly processes in construction, by carrying out an investigation into the stabilization of lateritic soil using Periwinkles Shell Powder (PSP). As much as the incorporation of PSP can help improve clean process in construction, it is not widely available across Africa and non-coastal areas.…”
Section: Previous Workmentioning
confidence: 99%
“…Snail shells, obtained as a byproduct from the consumption of snails, contain calcium carbonate, a mineral known to enhance soil strength and stiffness. Research has shown that the addition of pulverized snail shells to the soil can has the potential to improve its engineering properties [11], [13]- [15], thereby reducing the need for a higher lime content [11], [16]. This eco-friendly approach not only offers a cost-effective solution but also contributes to waste reduction and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Such subgrade problem soils could be expansive, collapsible, dispersive, soft clay and saline soils which causes detrimental effects to buildings and road structures. Low shear strengths, which are further reduced when wet or under other physical disturbances, are features of clays that are often undesirable in engineering [2]. When the subgrade soil sample obtainable for highway construction is not acceptable for the planned intents, soil stabilisation is necessary.…”
Section: Introductionmentioning
confidence: 99%